Les trajectoires spatiales d’activité des couples - Eva Lelièvre; Nicolas Robette (Temporalités)
After an overview of recent trends in data collection and of the different strategies applied to the demographic analysis of life courses embedded in their context, this paper presents the analysis of a specific level of interpersonal interaction : the intertwined dynamics of the life courses of both members of a couple. To this end, we reconstruct the dynamics of the activity space of couples defined as the territory covered by their place(s) of residence and place(s) of work since the beginning of their union, taking advantage of a rich data source, the INED Biographies et entourage survey. We then detail the principles of the data analysis method (Qualitative Harmonic Analysis). The description drawn from the typology obtained sheds light on the choices couples make for their residential moves, taking into account their family and occupational priorities. The limits of the method and future research paths are then discussed in the conclusion.